Evolving hybrid approaches: the preservation of the 'neglected' pulmonary valve function in patients with congenital heart disease. (2nd July 2016) - Vida, Vladimiro L.; Bacha, Emile; Stellin, Giovanni
ABSTRACT: The involvement of the hemodynamic expertise in the operating room led to the development of new strategies aimed to improve both early and long-term outcome of patients with congenital heart disease. During the last decade, with the aim of preserving the pulmonary valve function, we embarked on a new surgical approach, which combines surgical and interventional techniques, which are performed in the operating room. We believe that the preservation of the pulmonary valve function can be extended to any patients with classic tetralogy of Fallot and other selected patients with congenital pulmonary valve hypoplasia and dysfunction.